2011
DOI: 10.1177/0954420711413656
|View full text |Cite
|
Sign up to set email alerts
|

New discoveries in ultrasonic consolidation nano-structures using emerging analysis techniques

Abstract: This paper examines the influence of ultrasonic consolidation (UC) on the bonding interface and challenges existing opinion regarding the mechanism of oxide dispersal during UC bond formation. The findings presented in this paper were achieved through the use of dual beam focused ion beam (DBFIB) etching and transmission electron microscopy (TEM), enabling the close examination of the weld interface, sub-grain morphology, and dislocation structure in ultrasonically consolidated aluminium (Al) 3003-T0 samples.A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
(30 reference statements)
1
10
0
Order By: Relevance
“…This early recrystallization and grain refinement is the first contribution to the microstructure and texture evolution at the welding interface. Grain refinement from the sonotrode had also been reported by Kuo et al [18] on the top of 4130 steel foil and by Johnson et al [68] on the top of Al 3003 O. Study from Dehoff and Babu [56] showed that the interaction between the sonotrode and the top surface of the foil during UAM process was very important for the following UAM process from two aspects.…”
Section: Microstructure and Texture Change During Uammentioning
confidence: 55%
See 1 more Smart Citation
“…This early recrystallization and grain refinement is the first contribution to the microstructure and texture evolution at the welding interface. Grain refinement from the sonotrode had also been reported by Kuo et al [18] on the top of 4130 steel foil and by Johnson et al [68] on the top of Al 3003 O. Study from Dehoff and Babu [56] showed that the interaction between the sonotrode and the top surface of the foil during UAM process was very important for the following UAM process from two aspects.…”
Section: Microstructure and Texture Change During Uammentioning
confidence: 55%
“…Research from Johnson [44] also reported the grain refinement around the welding interface for Al 3003 O parts fabricated by ultrasonic consolidation. Johnson et al [68] demonstrated that the level of subgrain refinement in ultrasonically consolidated components was seen to decrease as the distance from the weld interface increased.…”
Section: Microstructure and Texture Change During Uammentioning
confidence: 99%
“…The modified topology of the sonotrode is necessary to efficiently transfer kinetic energy to the bond interface during the oscillations and weld pressure and to induce sufficient plastic flow for bonding (Friel et al, 2010a;Johnson, 2008;Johnson et al, 2011;Li and Soar, 2009). The roughened surface creates a mechanical coupling and prevents energy loss through slippage (Weare et al, 1960).…”
Section: Sonotrode Topologymentioning
confidence: 99%
“…Image reproduced courtesy of SAGE Publications(Johnson et al, 2011). Image reproduced courtesy of SAGE Publications(Johnson et al, 2011).…”
mentioning
confidence: 99%
“…How ever, high volumes of fibers may weaken the bond formation [7]. It has also been shown that the area in contact with the sonotrode exhibits grain refinement [6] which is restricted to a small area at the interface between the foils [5, 6,11]. To reduce the required amplitude and necessary matrix plastic flow, it was proposed to produce channels in UC samples to aid the placement and security during future fiber embedment via laser processing.…”
Section: Introductionmentioning
confidence: 99%